Coliving, a housing alternative? The case of the city of Malaga - Romero-Padilla, José; Romero-Padilla, Yolanda (Revista de Estudios Andaluces, 2025)
The difficulty of access to housing in Spain motivates the emergence of new housing alternatives. This study analyzes the implications of the coliving phenomenon in the city of Malaga. To do so, we have reviewed the scientific literature, coliving web portals, socioeconomic data and reviewed its regulations. All this together with a series of interviews with experts. The results show the absence of regulations in this regard in Spain, being young people and digital nomads are usually the target audience. The main conclusion is that it can facilitate access to housing, especially for young people and the establishment of digital nomads, given the current market circumstances. But it is essential to have an appropriate legal framework.